2021
DOI: 10.5194/bg-2021-321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suspended Particulate Matter drives the spatial segregation of nitrogen turnover along the hyper-turbid Ems estuary

Abstract: Abstract. Estuaries are nutrient filters and change riverine nutrient loads before they reach coastal oceans. They have been extensively changed by anthropogenic activities like draining, deepening, and dredging to meet economic and social demand, causing significant regime changes like tidal amplifications and in some cases to hyper-turbid conditions. Furthermore, increased nutrient loads, especially nitrogen, mainly by agriculture cause coastal eutrophication. Estuaries can either act as a sink or as a sourc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 83 publications
(105 reference statements)
1
7
0
Order By: Relevance
“…Using the delta values, we calculated the relationship between δ 18 O and δ 15 N (δ 18 O:δ 15 N) in the tidal river (Fig. 3b), which comes with 0.483 very close to the slope of 0.5 (Kendall et al, 2007;Schulz et al, 2022) and supports the relevance of denitrification.…”
Section: Along the Estuarysupporting
confidence: 57%
See 3 more Smart Citations
“…Using the delta values, we calculated the relationship between δ 18 O and δ 15 N (δ 18 O:δ 15 N) in the tidal river (Fig. 3b), which comes with 0.483 very close to the slope of 0.5 (Kendall et al, 2007;Schulz et al, 2022) and supports the relevance of denitrification.…”
Section: Along the Estuarysupporting
confidence: 57%
“…In a recent study, Schulz et al (2022) identified a dominance of denitrification with nitrification as an additional contributor in our focus area, the tidal river. They found δ 15 N values between 15 and 30 ‰ and suggested that these were caused by denitrification as the dominant process according to Kendall et al (2007), visualized in Fig.…”
Section: Along the Estuarymentioning
confidence: 92%
See 2 more Smart Citations
“…High variation in water column denitrification rates have been previously observed in suspended sediments of streambed origin across rivers of contrasting size (Reisinger et al, 2016). Recent work has emphasized the role of heterogeneous anoxic/hypoxic microsites on the activation of anaerobic microbial activity in suspended sediments (Zhu et al, 2018;Schulz et al, 2022). We contend that large variation in denitrification and Álvarez-Cobelas, 2006).…”
Section: Discussionmentioning
confidence: 65%